2022
DOI: 10.1002/hep.32478
|View full text |Cite
|
Sign up to set email alerts
|

IL‐1 receptor antagonist plus pentoxifylline and zinc for severe alcohol‐associated hepatitis

Abstract: Background and Aims Patients with severe alcohol‐associated hepatitis (AH) have high mortality. Corticosteroids improve survival only for 30 days. We targeted inflammation, cellular injury, and gut leakiness in a randomized clinical trial comparing combination therapy to corticosteroids on 180‐day survival. Approach and Results Subjects with a clinical diagnosis of severe AH (Model for End‐Stage Liver Disease [MELD] >20, Maddrey discriminant function [MDF] >32) were randomized to receive methylprednisolone (PR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
46
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 65 publications
(51 citation statements)
references
References 39 publications
4
46
0
1
Order By: Relevance
“…In the present edition of Hepatology , Szabo et al report on a RCT consisting of a 28‐day course of methylprednisone or a combination treatment of pentoxifylline, zinc, and anakinra in patients with severe AH. [ 5 ] The combination was intended to address three putative drivers of illness in AH: renal failure, increased gut permeability, and cytokine‐mediated inflammatory injury. The primary endpoint was survival at 6 months.…”
mentioning
confidence: 99%
“…In the present edition of Hepatology , Szabo et al report on a RCT consisting of a 28‐day course of methylprednisone or a combination treatment of pentoxifylline, zinc, and anakinra in patients with severe AH. [ 5 ] The combination was intended to address three putative drivers of illness in AH: renal failure, increased gut permeability, and cytokine‐mediated inflammatory injury. The primary endpoint was survival at 6 months.…”
mentioning
confidence: 99%
“…Anakinra is thought to have the potential to ameliorate liver injuries by blocking the IL-1β receptors [ 15 , 23 ]. The recent DASH trial confirmed that together with pentoxifylline and zinc, anakinra produced survival benefits similar to corticosteroids [ 17 ]. We included zinc supplements in the treatment as it is often deficient in patients with ALD [ 24 ].…”
Section: Methodsmentioning
confidence: 99%
“…This strategy was put to the test in a recent clinical trial. The Defeat Alcoholic Steatohepatitis (DASH) trial was a multicenter randomized controlled trial evaluating the effects of a combination of anakinra, an IL-1β receptor antagonist, pentoxifylline, and zinc vs. methyl-prednisolone on 30 and 90-day mortality in patients with severe AH [ 17 ]. When DASH investigators designed their trial, STOPAH results had not been published.…”
Section: Introductionmentioning
confidence: 99%
“…Combined treatment of pentoxifylline and corticosteroid has been examined in patients with AH, based on their different modes of action; however, the combination turned out to be ineffective in improving the survival rate of patients in a large randomized controlled trial [ 122 ]. Likewise, the use of pentoxifylline in combination with Anakinra, an IL-1 receptor antagonist, plus zinc showed similar survival benefits compared to methylprednisolone treatment in patients with severe AH [ 123 ]. Further, another large randomized controlled study (STOPAH) has demonstrated that patients treated with pentoxifylline showed no effect compared to the placebo group in terms of short-term mortality [ 11 ].…”
Section: Therapeutic Options For Various Stages Of Aldmentioning
confidence: 99%